Solve for t (complex solution)
t=\frac{2}{5}=0.4
t=-\frac{2}{5}=-0.4
t=-\frac{2\sqrt{2}i}{5}\approx -0-0.565685425i
t=\frac{2\sqrt{2}i}{5}\approx 0.565685425i
Solve for t
t=-\frac{2}{5}=-0.4
t=\frac{2}{5}=0.4
Share
Copied to clipboard
4t^{2}+25t^{4}-\frac{32}{25}=0
Subtract \frac{32}{25} from both sides.
25t^{2}+4t-\frac{32}{25}=0
Substitute t for t^{2}.
t=\frac{-4±\sqrt{4^{2}-4\times 25\left(-\frac{32}{25}\right)}}{2\times 25}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 25 for a, 4 for b, and -\frac{32}{25} for c in the quadratic formula.
t=\frac{-4±12}{50}
Do the calculations.
t=\frac{4}{25} t=-\frac{8}{25}
Solve the equation t=\frac{-4±12}{50} when ± is plus and when ± is minus.
t=-\frac{2}{5} t=\frac{2}{5} t=-\frac{2\sqrt{2}i}{5} t=\frac{2\sqrt{2}i}{5}
Since t=t^{2}, the solutions are obtained by evaluating t=±\sqrt{t} for each t.
4t^{2}+25t^{4}-\frac{32}{25}=0
Subtract \frac{32}{25} from both sides.
25t^{2}+4t-\frac{32}{25}=0
Substitute t for t^{2}.
t=\frac{-4±\sqrt{4^{2}-4\times 25\left(-\frac{32}{25}\right)}}{2\times 25}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 25 for a, 4 for b, and -\frac{32}{25} for c in the quadratic formula.
t=\frac{-4±12}{50}
Do the calculations.
t=\frac{4}{25} t=-\frac{8}{25}
Solve the equation t=\frac{-4±12}{50} when ± is plus and when ± is minus.
t=\frac{2}{5} t=-\frac{2}{5}
Since t=t^{2}, the solutions are obtained by evaluating t=±\sqrt{t} for positive t.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}